2014
DOI: 10.3389/fgene.2014.00337
|View full text |Cite
|
Sign up to set email alerts
|

A non-canonical landscape of the microRNA system

Abstract: Microribonucleic acids, best known as microRNAs or miRNAs, are small, non-coding RNAs with important regulatory roles in eukaryotic cells. Here, I present a broad review on highly relevant but generally non-depicted features of miRNAs, among which stand out the non-conventional miRNA seed sites, the unusual messenger RNA (mRNA) target regions, the non-canonical miRNA-guided mechanisms of gene expression regulation, and the recently identified new class of miRNA ligands. Furthermore, I address the miRNA uncommo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 82 publications
0
43
0
1
Order By: Relevance
“…The kinaseactivating LRRK2 mutant G2019S is reported to increase translation activity in Drosophila [20,21] using both direct and indirect measures for overall translation activity and protein translation reporter systems. In a related mechanism, LRRK2 interacts with argonaute proteins [24], which are essential components of miRNA machinery, regulating protein expression levels by inhibition of translation or degradation of mRNA [25,26]. Therefore, LRRK2 may intervene in regulating protein expression via multiple mechanisms.Interestingly, several recessive PD genes such as PRKN, PINK1, and DJ-1, which cause early-onset forms of PD, are also reported to influence protein translation.…”
Section: Genetic Links Between Pd and Protein Translationmentioning
confidence: 97%
“…The kinaseactivating LRRK2 mutant G2019S is reported to increase translation activity in Drosophila [20,21] using both direct and indirect measures for overall translation activity and protein translation reporter systems. In a related mechanism, LRRK2 interacts with argonaute proteins [24], which are essential components of miRNA machinery, regulating protein expression levels by inhibition of translation or degradation of mRNA [25,26]. Therefore, LRRK2 may intervene in regulating protein expression via multiple mechanisms.Interestingly, several recessive PD genes such as PRKN, PINK1, and DJ-1, which cause early-onset forms of PD, are also reported to influence protein translation.…”
Section: Genetic Links Between Pd and Protein Translationmentioning
confidence: 97%
“…There is large variety of miRNA-target duplex structures, which include seedless interactions (reviewed in (Cipolla, 2014;Seok et al, 2016a)). The existence of seedless interactions explains reports that perfect seed pairing is not a generally reliable predictor for miRNA-target interactions (Didiano and Hobert, 2006).…”
Section: Non-canonical -Non-seed Interactionsmentioning
confidence: 99%
“…Particularly, miRNAs have been found to regulate the stability of nuclear transcripts (e.g. mRNAs, long non-coding RNAs (lncRNAs) or pri-miRNAs), induce epigenetic alterations at specific gene promoters, and likely modulate alternative splicing events in the nuclear compartment [22][23][24][25][26]. Moreover, two studies have reported few specific miRNAs as ligands for toll-like receptor (TLRs; TLR7 in mice and TLR8 in humans) activation [27,28].…”
Section: Mirna Biogenesis and Biological Functionmentioning
confidence: 99%
“…Although the central role of miRNAs is to negatively regulate protein synthesis, other functions of miRNAs are emerging (reviewed in [22] and [23]). Particularly, miRNAs have been found to regulate the stability of nuclear transcripts (e.g.…”
Section: Mirna Biogenesis and Biological Functionmentioning
confidence: 99%